Video Mpo Alpa dan Fenomena Selebritis Online Indonesia - Nurhablisyah, Nurhablisyah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2018)
In the beginning of year 2018, Indonesiaâ€™s netizen was mesmerized by viral viedo which captured a woman with thick make up talking by herself about her feeling toward her husband. That woman eagered to go to the mall depite of her busyness doing a house chore and economical pressure, insist her husband to company her. Netizen was amazed by the Betawi dialect she was spoken and the funny content she told. In a short periode, the video became massive viral, and turn another nertizens made the same video. The video is mostly about sharing your personal experience with your wife or husband. The lady in the Video known as â€œMpok Alpaâ€ then got public and media intention. She was invited to several media as a guest in television programme, launch a single called â€œKe Emolâ€ and even hored to have role in tv series. Mpok Alpa is not the only one, who started her career as celebrity from social media. Mpok Alpa Shortly become celebrity know as â€œSelebgramâ€ or online celebrity. They use their popularity in online media to influence and selling to netizen. By having a huge fan base in their social media accounts, these celebrity also targeted by company to became their brand ambassador and star.